2009
DOI: 10.1111/j.1540-6237.2009.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Same‐Sex Marriage and Negative Externalities*

Abstract: Conventional theory regarding externalities and personal choices implies that in the absence of negative externalities, there is no economic rationale for government to regulate or ban those choices. We evaluate whether legally recognizing (or prohibiting) same-sex marriage has any adverse impact on societal outcomes specifically related to "traditional family values." Copyright (c) 2009 by the Southwestern Social Science Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 9 publications
1
38
1
Order By: Relevance
“…Our article adds to a small but growing literature on marriage-like contracts for same-sex couples afforded by the recent expansion of such rights (Burn and Jackson 2014;Carpenter and Gates 2008;Dillender 2014Dillender , 2015Langbein and Yost 2009;Trandafir 2015). Exploiting cross-sectional and time variation, a number of studies have found no evidence of the legalization of same-sex unions eroding traditional values as measured by marriage, divorce, or abortion rates.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our article adds to a small but growing literature on marriage-like contracts for same-sex couples afforded by the recent expansion of such rights (Burn and Jackson 2014;Carpenter and Gates 2008;Dillender 2014Dillender , 2015Langbein and Yost 2009;Trandafir 2015). Exploiting cross-sectional and time variation, a number of studies have found no evidence of the legalization of same-sex unions eroding traditional values as measured by marriage, divorce, or abortion rates.…”
Section: Introductionmentioning
confidence: 89%
“…In that period, State-sanctioned persecution of Jews, lepers, male homosexuals, and heretics emerged to form what Moore (2007) coined "the prosecuting society." 4 For the United States, see Langbein andYost (2009) andDillender (2014). For the OECD, see Trandafir (2015).…”
Section: Introductionmentioning
confidence: 98%
“…Allen (2015 ) has observed that "A proper probability sample is a necessary condition for making a general claim about an unknown population, based on a sample" (p. 159). Langbein and Yost (2009 ) tested fi ve possible outcomes of legalization of same-sex marriage; fi nding no relationship between some sort of same-sex legal unions in a state and those selected outcomes, they deemed that there were no "negative externalities" associated with same-sex marriage. However, proving that fi ve variables are not signifi cantly related to a predictor variable does not mean that there are no other variables yet to be found signifi cant; that is an improper generalization.…”
Section: Poorly Described Non-blinded or Biased Samplesmentioning
confidence: 99%
“…Similarly, in part due to religious pluralism as well as greater moral latitude in some Christian denominations, the symbolic value of being Christian has decreased historically in the country, and the symbolic value of some traits previously associated with Christianity has also diminished. For example, homosexuals are increasingly asserting their rights and encroaching on privileges previously isolated to heterosexuals, such as marriage (Stadler 2009; Langbein and Yost 2009;Lewin 2008). Hence, it appears that one purpose of the identity formations of these conservative social movements is to reclaim this lost symbolic capital by restricting access to privileges to a smaller number of "true" Americans and Christians.…”
Section: Resultsmentioning
confidence: 94%